Question: product rule for log in Maple

How could one tell Maple to simplify  log(x)+log(y) to log(x*y)?

As Maple own apps says

And known identity


This is what I tried

simplify( ln(x) + ln(y), symbolic);
simplify( ln(x) + ln(y), ln);
simplify( ln(x) + ln(y), size);

Maple knows this identity, becuase

simplify( ln(x*y)- (ln(x)+ln(y)) , symbolic)

Note, this identity has no assumptions on it. It is defined as is.

Maple help page says

ln(x y) ==> ln(x) + ln(y) provided     0 < x  and   signum(y) is unknown

so, is Wikipedia and all the other references I saw wrong for not showing this assumption on x>0 whey they state the product rule for logs?

I want to go the other way

 ln(x) + ln(y) ==> ln(x y) 

So this releation should really be written as

ln(x) + ln(y) <==> ln(x y) 


Please Wait...